BEARINGS WITH THE BUILT IN DIAGNOSTIC AIDS AND OPERATED KINEMATICS - A. L. Savchenko; N. T. Minchenya; V. T. Minchenya; R. M. Asimov (Приборы и методы измерений)
The concept and possible variants of mechatronic bearings designs of the fourth generation with sensors of angular position and tiny vibroresonance drives for kinematics management during the working process, with built-in diagnostics aid functioning on the basis of the analysis of separator rotation speed fluctuations have been offered.